The Role of Leadership Capacity in Strengthening Trust Among Members in Jabres Cattle Farmer Groups in Brebes Regency, Indonesia - Sugiarto, Mochamad; Cahyo, Danang Nur (Faculty of Animal Science, Universitas Brawijaya, 2025)
This study explores the leadership capacity in strengthening trust among members of Jabres cattle farmer groups in Brebes Regency. Internal dynamics, including the quality of leadership within the groups, greatly influence the success of these farmer groups. Strong leadership capacity can enhance communication, coordination, and collaboration effectiveness, strengthening members’ trust. The study employed a survey method with 119 respondents selected through multistage random sampling from various Jabres cattle farmer groups in the regency. Data were analyzed using Spearman's rank correlation to test the relationship between leadership capacity and member trust. The results showed a significant positive relationship between leadership capacity and trust (p<0.01). These findings emphasize the importance of developing the leadership capacity of group leaders in strengthening trust among members, which ultimately supports the performance and sustainability of the cattle farmer groups.